Concomitant Heart Surgery with Pulmonary Hamartoma Resection: A Case Report - Niyazi Görmüş; Ömer Tanyeli; Atilla Orhan (Genel Tıp Dergisi)
Concomitant lesions of the heart and lung are rare, but when present, they pose a therapeutic challenge to surgeons. A combined procedure clears the need for a second major procedure, improving outcomes and providing economic benefits. However, cardiopulmonary bypass may adversely affect the natural history of pulmonary masses when malignancy is suspected. To avoid these suspects, off-pump techniques may be preferred in suitable patients. This article presents a case of simultaneous off-pump coronary artery bypass grafting and pulmonary hamartoma resection in a 53-year-old man who detected a lung mass during preoperative preparation.